Perbandingan Daya Lekat Pewarna Ekstrak Daging Buah Naga Merah dan Kulit Manggis dengan Disclosing Solution - Muhammad Faisal; Zulfikri Zulfikri (Universitas Batanghari Jambi, 2023)
Dental plaque is a bacterial biofilm structure, neatly organized and attached to the tooth surface, which contains inorganic components such as calcium and phosphorus derived from saliva. Bacteria in plaque that stick to the surface of the teeth will provide a place for new bacteria to grow. Disclosing solution is a plaque coloring agent that works to change the color of dental plaque to contrast with the color of the white tooth surface. Erythrosine is a red coloring agent commonly used for disclosing solutions, but erythrosine is a synthetic dye which is carcinogenic. Anthocyanins are natural dyes that have met the requirements as additional food coloring agents, which are internationally permitted as food coloring agents. This study aims to determine the adhesive power comparison of red dragon fruit peel extract (Hylocereus costaricencis) and mangosteen rind extract (Garcinia mangostana) with a disclosing solution made in manufactured. The research design was an experiment conducted at the Dwi Farma Pharmacy Laboratory in Bukittinggi. The research was conducted in November 2020. This research was conducted on 10 preparations. Analysis of the results of the study used the t test independent with a 95% confidence level and a significance level at Î± = 0.05. Statistical test results showed that there was a difference in the average length of adhesion between mangosteen rind extract and disclosing solution, between red dragon fruit peel extract and disclosing solution, and between mangosteen rind extract and red dragon fruit peel. A comparison of the duration of adhesion of mangosteen peel extract and red dragon fruit peel extract showed that the average duration of adhesion of mangosteen rind extract was faster than that of red dragon fruit peel extract and factory-made disclosing solution.